OUTDOOR BASED ENVIRONMENTAL EDUCATION LEARNING AND ITS EFFECT IN CARING ATTITUDE TOWARD ENVIRONMENT (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
A study of outdoor learning based on the instructions on environmental education for prospective of the elementary school teachers was carried out to encouragethem to improve their view on the environmental literacy in taking care of school environment. The research method used is based on the research and development method. From the research, we can found that: (1) the improvement of concept mastery in the environmental education was better than the regular class, (2) the performance and attitude of the prospective teachersof the elementary school was in a good category (3) reviews their ability in implementing outdoor based instruction was in a good category (4) reviews their attitude in taking care of the school environment was in a very good category.